The Impact Of Developing The Beji Temple Tourist Attraction On The Local Economy Of Sangsit Village, Sawan Subdistrict, Buleleng Regency - Luh De Meire Rogista Wulandari; Nyoman Danendra Putra; I Gusti Ayu Putu Novita Sari Paragae; Luh Oka Puji Apsari4 (International Journal of Entrepreneurship and Tourism, 2025)
Beji Temple, a culturally significant heritage site in Sangsit Village, Buleleng Regency, is a key tourist attraction. This study examines the impact of its tourism development on the local economy. Using a qualitative descriptive approach, data was collected through field observation, in-depth interviews with eight key informants (including the Village Head and local businesses), and documentation. Analysis was framed by Multiplier Effect Theory, Tourism Impact Theory, and Sustainable Tourism Theory. Findings reveal significant positive economic impacts, particularly boosting culinary businesses like coffee shops, young coconut ice, rujak kuah pindang, blayag, sausages, and soto. Ancillary services such as parking and kamen rentals for worshippers also benefit. However, other potential sectors like tour guiding, transportation rentals, and accommodation remain underdeveloped. Key constraints include a lack of trained personnel, insufficient supporting facilities, and limited professional tourism promotion. To maximize sustainable benefits, increased income, new job creation, and local empowerment, more intensive collaboration is crucial. This requires concerted efforts between the village government, tourism office, cultural office, and active participation from the local community.